Characterization of Flavonoids From Seed Coat of Bauhinia racemosa - Swanti Jain, Km.; Pathak, Vishal; Srivastava, B.K. (Asian Journal of Chemistry, 2010)
In the present paper we are reporting the characterization of flavonoids from the seed of Bauhinia racemosa by spectral study.